Consumer Behavior in the Age of AI: The Role of Personalized Marketing and Data Analytics in Shaping Purchase Decisions - Izharuddin Pagala; Muhammad Asir; Klemens Mere; Utami Puji Lestari; Heidi Siddiqa (Dinasti Publisher, 2024)
In the contemporary digital era, artificial intelligence (AI) has revolutionized the landscape of consumer behavior by enabling personalized marketing and advanced data analytics. This article reviews existing literature to explore the role of AI in shaping purchase decisions. The emergence of AI technologies allows marketers to leverage vast amounts of consumer data to create personalized experiences, enhancing customer engagement and satisfaction. Through personalized marketing strategies, companies can deliver tailored content, product recommendations, and targeted advertisements that align with individual consumer preferences. The integration of data analytics provides deeper insights into consumer behavior, enabling businesses to anticipate trends and make informed decisions. This literature review examines various case studies and empirical research to highlight the effectiveness of AI-driven marketing strategies in influencing consumer purchase decisions. The findings indicate that personalized marketing, underpinned by sophisticated data analytics, not only enhances consumer trust and loyalty but also drives higher conversion rates. This study underscores the importance of embracing AI technologies for businesses aiming to stay competitive in an increasingly digital marketplace.